Electron microscopy of nanoemulsions: An essential tool for characterisation and stability assessment - Klang, Victoria; Matsko, Nadejda B.; Valenta, Claudia; Hofer, Ferdinand (Micron (Oxford, England : 1993), 2012)
► Electron microscopy is essential for the characterisation of nanoemulsions. ► Nanoemulsion morphology can be visualised by both TEM and SEM. ► Cryogenic EM techniques deliver images of nanoemulsions in their native state. The characterisation of pharmaceutical formulations by microscopic techniques is essential to obtain reliable data about the actual morphology of the system. Since the size range of colloidal drug delivery systems has long ago reached the lower end of the nanometer scale, classical light microscopy has been replaced by electron microscopy techniques which provide sufficient resolution for the visualisation of nano-sized structures. Indeed, the superior resolution and methodological versatility of electron microscopy has rendered this technique an indispensable tool for the analysis of nanoemulsions. Microscopic analysis of these lipid-based drug delivery systems with particle sizes in the lower submicron range provides critical information about the size, shape and internal structure of the emulsion droplets. Moreover, surfactant aggregates such as liposomes or multilamellar structures which remain unnoticed during particle size measurements can be detected in this fashion. This review provides a brief overview about both transmission electron microscopy (TEM) and scanning electron microscopy (SEM) techniques which have been employed to characterise nanoemulsions. Of special interest are sophisticated cryo techniques of sample preparation for both TEM and SEM which deliver high-quality images of nanoemulsions in their natural state. An overview about the instrumentation and sample preparation for all presented methods is given. Important practical aspects, sources of error and common artefacts as well as recent methodological advances are discussed. Selected examples of electron microscopic studies of nanoemulsions are presented to illustrate the potential of this technique to reveal detailed and specific information.